PROBLEMS OF FUNCTIONING OF THE TAX CONTROL SYSTEM IN UKRAINE (Economic journal of Lesya Ukrainka Volyn National University, 2021)
The paper is devoted to the study of the problems of the tax control system in Ukraine, the solution of which will contribute to the effective development of the financial system and the economy as a whole, as well as its economic security. It is proved that tax control relies on checking compliance with tax legislation, correctness of calculation, completeness and timeliness of payment of taxes and fees, prosecution of perpetrators of violations, as well as prevention of violations of tax legislation. The functions, tasks and strategic goals of the Tax Audit Department of the State Tax Service of Ukraine, which is authorized to carry out control and verification work on legal entities and individuals, have been determined. The reporting data on the control and verification work of the State Tax Service of Ukraine was considered and the reduction of the tax burden on taxpayers in recent years was revealed due to the introduction in 2020 of a partial moratorium on documentary and factual inspections. The main problems that complicate the effective functioning of the current system of tax control are generalized; in particular, attention is focused on the low tax culture and distrust of taxpayers to regulatory authorities. The data on the quality of work of employees of controlling bodies were studied, on the basis of which a high level of appeal and cancellation of monetary obligations on the materials of inspections was revealed, in particular due to poor inspection, failure to prove established violations and due to ambiguous interpretation of tax legislation. Priority areas for improving the domestic tax control system have been developed, primarily due to the harmonization of relations between regulatory authorities and taxpayers. their evasion of tax liability and, as a consequence, filling the revenue side of the budget.
Keywords: tax system, controlling bodies, tax inspections, tax evasion, tax culture